Why do sport coaches adopt a controlling coaching style? The role of an evaluative context and psychological need frustration - Morbée, S.; Vansteenkiste, M.; Aelterman, N.; Haerens, L. (The Sport Psychologist, 2020)
In this study, involving 585 youth sport coaches (M age = 35.76), the authors investigated whether coaches who perceive their environment to be highly evaluative would report acting in a more controlling or pressuring way. In a subsample (n = 211, M age = 38.14), they examined the explanatory role of coaches` experiences of psychological need frustration in this relation. They also considered whether years of coaching experience would serve as a buffer against the adverse effects of an evaluative context. In line with the tenets of self-determination theory, results of structural equation modeling indicated that an evaluative context was related to the use of a more controlling coaching style, with experiences of need frustration accounting for this relation. Coaching experience did not play any moderating role, suggesting that even more experienced coaches are vulnerable to the harmful correlates of an evaluative sport context.